Dilemmas of the Communication Consultant Abroad - Francis C. Byrnes (Journal of Applied Communications, 1984)
When first invited to talk here, I suggested the title: "Mom, are them green things oranges?" While neither professional nor academic, the title rather vividly describes the "Dilemmas of the Communication Consultant Abroad."